Mental health reforms in the Czech Republic - Pec, Ondrej (BJPsych international, 2019)
This paper describes the history and current provision of mental healthcare in the Czech Republic. After the political changes in 1989, there was an expansion of out-patient care and several non-governmental organisations began to provide social rehabilitation services, but the main focus of care still rested on mental hospitals. In recent years, mental health reform has been in progress, which has involved expanding community-based services and psychiatric wards of general hospitals, simultaneously with educational and destigmatisation programmes.